CONTEXTUALIZATION OF PRIMORDIAL MARYAM IN COLLECTIONS OF HANDSOME LOVE POEMS WORKS OF A. MUSTOFA BISRI - Nurfiana, Efen (Lembaga Kajian Nusantara Raya (LK Nura), 2023)
This study seeks to perceive the concept of mother's love in Rumi's view, namely Maryam Primordial, a mother who takes care of her children through A. Mustofa Bisri's Love Poems of Love. This study utilizes Paul Ricoeur's interpretation through three kinds of text autonomy, namely text, context and contextualization. Based on his interpretation, this study found that A. Mustofa Bisri identifies mother's love in the form of affection by caring for, protecting and providing assurance. As the output of this identification, namely carrying out 'amar ma'ruf nahi munkar, in order to achieve noble ideals, the path to God, namely world jewelry, a pious woman.